Possible Role of Phenolics and Flavonoids in Antioxidant, Cytotoxic and Thrombolytic Activities of Eclipta prostata L. (Bangladesh Pharmaceutical Journal, 2022)
Eclipta prostata (E. prostata) L, is a herbal medicinal plant, which is reported to contain phenolics and flavonoids, but very little is known about its bioactive potentials. In this report, we reexamined the phenols and flavonoid content and evaluated different bioactivities of organic soluble fractions from the shoots of E. prostata for the first time. Among the extractives, chloroform soluble fraction (CSF) possessed the highest content of phenols (156.03 ± 0.52 mg gallic acid equivalent /g of dry extract) and flavonoids (67.47 ± 0.56 mg quercetin equivalent /g of dry extract) and exhibited the most potent antioxidant properties in terms of total antioxidant capacity (198.71 ± 0.89 mg ascorbic acid equivalent/g of dry extract) and DPPH free radical scavenging ability (IC50; 17.68 ± 0.32 μg/ml). Similarly, CSF showed the highest cytotoxicity with LC50 values of 16.03±0.23 μg/ml, and thrombolytic activity with 36.06 ± 0.39% clot lysis. A significant correlation was observed between flavonoid content and total antioxidant capacity (r2 = 0.894, p < 0.05), while high correlation was seen between polyphenols and flavonoid content with free radical scavenging, total antioxidant capacity and cytotoxicity (r2 = 0.612 - 0.928). These findings suggest that E. prostata is a precious source of polyphenols having potential bioactivities, which could be utilized for the management of lifestyle diseases.Bangladesh Pharmaceutical Journal 25(2): 164-174, 2022 (July)